The Influence of Price and E-WOM on Millennial Generation Purchase Interest at InterContinental Bali Resort - Atmaja, I Putu Gede Brandon Wira; Pitanatri, Putu Diah Sastri; Adyatma, Prastha (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study aims to determine the effect of price and e-WOM on the purchase intention of the millennial generation at the InterContinental Bali Resort. The population is the millennial generation who have accessed information about the InterContinental Bali Resort using the Google platform, and have never stayed at the InterContinental Bali Resort. The sample used was 100 respondents with a data collection method using a questionnaire, in the form of a Google Form. The data analysis techniques used in this study are Multiple Linear Regression Analysis, t-Test, F-Test, and Determination Coefficient Analysis. Based on the results of the study, it can be seen that price and e-WOM partially and simultaneously have a positive and significant effect on purchase intention. The magnitude of the influence of the price and e-WOM variables on purchase intention is 63.3% or can be said to be in the strong category.